Reconstructing the geographic and climatic origins of long‐distance bird migrations. (8th September 2019) - Dufour, Paul; Descamps, Sébastien; Chantepie, Stéphane; Renaud, Julien; Guéguen, Maya; Schiffers, Katja; Thuiller, Wilfried; Lavergne, Sébastien
Abstract: Aim: Seasonal bird migration is one of the most fascinating global ecological phenomena. Yet, the biogeographic scenarios and climatic drivers that led single species or entire lineages to evolve seasonal migration between disjunct breeding and wintering ranges remain unclear. Based on distribution and phylogenetic data for all birds worldwide, we explored the biogeographic and climatic context of the evolutionary emergence of seasonal geographic migration in birds. Location: Global. Taxon: The Aves class (9, 819 species). Methods: We used the worldwide phylogeny of all birds, with a new backbone tree, to test the link between birds' migration distance (short, variable, long) and strategy (resident, mixed, strict migrant) with four different metrics depicting species' thermal niches in their breeding and wintering ranges. We also performed ancestral state reconstructions for the main migratory orders to reconstruct past events of appearance and loss of migration behaviour, and past biogeographic scenarios that led to the emergence of seasonal geographic migration. Results: Migratory species generally experience warmer climates in their wintering range compared to their breeding one, although notable exceptions exist. This thermal niche change due to migration was found to be much larger for species travelling large distances. We also found that geographic migration emerged at different time periods through varied biogeographic paths (i.e. both from temperate and tropical ancestors) and that migration behaviour was likely ancestral to Passeriformes, with several subsequent episodes of loss of migration behaviour. Main conclusions: We report an evolutionary correlation between long‐distance migration and the tendency of birds to seek warmer climates during their non‐breeding period, compared to short‐distance migrants. Migration behaviour was likely ancestral to Passeriformes, and migratory lineages in general seem to have often adapted to novel ecological opportunities by returning to a resident state. Our results provide the first large‐scale study of biogeographic and climatic origins of bird migration worldwide.